ANALISIS FAKTOR PENYEBAB KEMATIAN PADA KECELAKAAN LALU LINTAS - Ismurrizal Ismurrizal (Jurnal Kajian Kesehatan Masyarakat, 2020)
Traffic accidents can lead to various injuries. The head is the body part most often affected by injuries in traffic accidents. This study aims to determine the relationship between age and gender with the incidence of head trauma in a traffic accident in the installation of Forensic and Medicolegal Hospital Dr. Pirngadi Medan. This type of research is descriptive research with cross sectional approach. Sampling using total sampling technique, with the number 116 is used as a sample case study. Data analysis using chi-square test. The results showed that there was no significant relationship (p = 0.479) between age and the incidence of head trauma in a traffic accident, the results also indicate that the there is no significant relationship (p) = 0.302 between the sexes with the incidence of head injuries in traffic accident cross.